FAKTOR – FAKTOR YANG MEMPENGARUHI KEJADIAN ANEMIA IBU HAMIL DI RUMAH BERSALIN CITRA - Anur Rohmin; Siti Amallia; Annisa Melinda; Desti Ayu (Jurnal Kesehatan dan Pembangunan, 2024)
Anemia in pregnant women increases the risk of Low Birth Weight (LBW) Babies, premature birth, maternal and infant deaths. The results of the 2018 Riskesdas show that the prevalence of anemia in pregnant women increased from 37.1% in 2013 to 48.9% in 2018. The aim of this research is to find out the factors that influence the incidence of anemia in pregnant women at the Citra Maternity Home. The methodology of this research is an analytical survey with a cross-sectional approach. The research sample was 94 pregnant women in the first, second and third trimesters who visited the Citra Maternity Home, taken using purposive sampling. This research was conducted on 11 September – 13 November 2022. The results of this study showed a significant relationship between gestational age (p-value: 0.014), Parity (p-value: 0.046), Pregnancy Distance (p-value: 0.019), and Compliance with taking Fe tablets (p-value: 0.009) with the incidence of anemia in pregnant women. The variable compliance with taking Fe tablets is the variable that most dominantly influences the incidence of anemia in pregnant women with OR. 2.9698: . The incidence of anemia in pregnant women is influenced by gestational age, parity, pregnancy spacing and adherence to taking Fe tablets, where adherence to taking Fe tablets is the dominant factor influencing the incidence of anemia in pregnant women. It is hoped that this research will increase education on Fe tablet supplementation in women of childbearing age and pregnant women to prevent anemia in pregnancy and carry out continuous pregnancy monitoring.